النوموفوبيا "الخوف من فقدان الهاتف المحمول" وعلاقته بنمط الحياة والصحة النفسية لدى عينة من المراهقين في ظل جائحة كورونا - عثمان، نورا أحمد الباز (جامعة عين شمس - كلية التربية, 2021)
هدفت الدراسة إلى التعرف على رهاب فقدان الهاتف المحمول (النوموفوبيا) وعلاقته بنمط الحياة والصحة النفسية لدى عينة من المراهقين، والتعرف على النوموفوبيا كمنبئ بنمط الحياة والصحة النفسية لدى عينة المراهقين، والكشف عن الفروق في النوموفوبيا تبعا لاختلاف النوع (ذكور- إناث)، والتخصص (أدبى وعلمي)، ومدة استخدام الهاتف المحمول، وتكونت عينة البحث من (٢٧٦) طالب وطالبة من طلاب المرحلة الثانوية تتراوح أعمارهم من (١٦ - ١٨) سنة، واستخدمت الباحثة مقياس النوموفوبيا إعداد / (Yildirim & Correia,2015) ​ترجمة وتعريب الباحثة، ومقياس نمط الحياة إعداد/الباحثة، ومقياس الصحة النفسية إعداد / الباحثة، وتوصلت نتائج الدراسة إلى وجود علاقة ذات دلالة إحصائية بين النوموفوبيا ونمط الحياة والصحة النفسية لدى عينة من المراهقين، كما أظهرت النتائج إسهام متغير النوموفوبيا في التنبؤ بنمط الحياة والصحة النفسية لدى عينة المراهقين، وتوصلت النتائج أيضا إلى عدم وجود فروق ذات دلالة إحصائية في أبعاد مقياس النوموفوبيا والدرجة الكلية وفقا لمتغير التخصص (علمي/أدبي) والنوع (ذكور/إناث)، ولكن أسفرت النتائج عن وجود فروق ذات دلالة إحصائية في مستوي النوموفوبيا وفقا لعدد ساعات استخدام الهاتف.
The study aimed to examine the relationship between Nomophobia and lifestyle and mental health among a sample of adolescents. The study also tried to examine the role played by Nomophobia as a predicator of life style and mental health, to identify. The study examined also the differences in Nomophobia according to the difference of gender (male - female), and specialization (arts vs. science), and the duration of mobile phone use. The sample consisted of 276 high school students ranging in age from (16-18) years, and the researcher used the nomophobia scale (Yildirim & Correia, 2015)) translated by the researcher, and the lifestyle scale and the mental health scale prepared the researcher. The results of the study showed a statistically significant relationship between nomophobia, lifestyle and mental health in a sample. The results showed the contribution of the nomophobia variable in predicting the lifestyle and mental health of a sample of adolescents. There are no statistically significant differences in the dimensions of the nomophobia scale and the total score according to the variable of specialization (scientific/literary) and gender (male/female), whereas there are statistically significant differences according to the number of hours of phone use in favor of heavy users with 6-8 hours.
Keywords: المراهقة -- المراهقين -- نمط الحياة -- الصحة النفسية -- الاضطرابات النفسية -- اضطراب النوموفوبيا -- رهاب فقدان الهاتف المحمول -- فيروس كورونا (كوفيد-19) -- طلبة المرحلة الثانوية